Nutrient Composition of Artocarpus champeden and Its Hybrid (Nanchem) in Negara Brunei Darussalam - L.B.L Lim; H.I Chieng; F.L Wimmer (ASEAN Journal on Science and Technology for Development, 2011)
The flesh and seeds of ripened and unripened Artocarpus champeden and its ripened hybrid (Nanchem) were analyzed for their moisture, ash, crude fibre, crude protein, crude fat, total carbohydrate, energy and mineral content. Generally, unripened A. champeden which is always treated and cooked as a vegetable contains higher amounts of moisture, ash, crude fibre and crude protein for its flesh than ripened A. champeden and Nanchem. Ripened A. champeden and Nanchemhave higher total carbohydrates and energy content than the unripe fruit. Similarly, the unripened A. champeden seed has more nutritional components in terms of moisture, ash, crude fibre, crude protein, crude fat, total carbohydrate and energy compared to the ripened A. champeden and Nanchem seeds. Potassium and magnesium are the prevalent minerals in this fruit species. Nanchem has the characteristics of both jackfruit (A. heterophyllus) and A. champeden.